O ensino jurídico na cidade de Macapá/AP e as novas tecnologias: diálogos com a andragogia. - Santos, Thiago de Sarges (2023)
In Brazil, education is legally established as a right for everyone and a duty of the State and the family, aiming at the full development of the person, preparation to exercise citizenship and qualification for work. Therefore, this research has the general objective of analyzing, in the light of Andragogy, how digital information and communication technologies have mediated the teaching and learning processes of legal education in higher education in the State of Amapá in the period from 2020 to 2021 The specific objectives are: to present the principles of education from the perspective of Andragogy; Identify how technology is being used in the teaching and learning process in Higher Education Institutions; and analyze the use of digital information and communication technologies in Law courses at educational institutions in Macapá, in the light of Andragogy, in the years 2020 and 2021. This is a descriptive research, qualitative in nature, technical collection procedures data multiple case study, carried out in five private colleges and a Federal University, from a sample of 100 students, using a questionnaire, with open and closed questions, to be answered via a form on Google Forms. The results indicated which policies are adopted by educational institutions and how relationships between educators, students and management are established.